Efficacy of Endoscopic Retrograde Cholangiopancreatography in the Treatment of Biliary Complications following Liver Transplant: 10 Years of a Single-Centre Experience - Alves,Ana Rita (2018)
Background and Aims: Biliary tract complications following liver transplant remain an important source of morbidity and mortality. Endoscopic retrograde cholangiopancreatography (ERCP) has become a common therapeutic option before other invasive procedures. The aim of this study was to evaluate ERCP efficacy in managing this type of complications. Methods: Retrospective study of all patients who underwent therapeutic ERCP due to post-liver transplant biliary complications between September 2005 and September 2015, at a deceased donor liver transplantation centre. Results: Therapeutic ERCP was performed in 120 patients (64% men; mean age 46 ± 14 years). Biliary complications were anastomotic strictures (AS) in 70%, non-anastomotic strictures (NAS) in 14%, bile leaks (BL) in 5.8%, and bile duct stones (BDS) in 32%. The mean time between liver transplant and first ERCP was: 19 ± 30 months in AS, 17 ± 30 months in NAS, 61 ± 28 months in BDS, and 0.7 ± 0.6 months in BL (p < 0.001). The number of ERCP performed per patient was: 3.8 ± 2.4 in AS, 3.8 ± 2.1 in NAS, 1.9 ± 1 in BDS, and 1.9 ± 0.5 in BL (p = 0.003). The duration of the treatment was: 18 ± 19 months in AS, 21 ± 17 months in NAS, 10 ± 10 months in BDS, and 4 ± 3 months in BL (p = 0.064). Overall, biliary complications were successfully managed by ERCP in 46% of cases, either as an isolated procedure (43%) or rendez-vous ERCP (3%). Per complication, ERCP was effective in 39% of AS, in 12% of NAS, in 91% of BDS, and in 86% of BL. Globally, the mean follow-up of the successful cases was 43 ± 31 months. Percutaneous transhepatic cholangiography and/or surgery were performed in 48% of patients in whom ERCP was unsuccessful. The odds ratio for effective endoscopic treatment was 0.2 for NAS (0.057-0.815), 12.4 for BDS (1.535-100.9), and 6.9 for BL (0.798-58.95). No statistical significance was found for AS (p = 0.247). Conclusions: ERCP allowed the treatment of biliary complication in about half of patients, avoiding a more invasive procedure. Endoscopic treatment was more effective for BDS and BL.